1996
DOI: 10.1002/art.1780390625
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in systemic lupus erythematosus

Abstract: Objective. To estimate the risk of cancer in patients with systemic lupus erythematosus (SLE).Methods. Patients with SLE (n = 724) have been followed prospectively, for 24 years, at the University of Toronto Lupus Clinic. The diagnosis of cancer was confirmed by histologic or autopsy reports. Standardized rates of cancer and standardized incidence rates (SIR) (ratio of observed-to-expected cancers) were used to estimate the risk for cancers.Results. Twenty-four cancers were identified in 23 SLE patients (3.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
98
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 13 publications
9
98
0
3
Order By: Relevance
“…The earliest clinical evidence of an association of cancer with systemic lupus erythematosus came from case and case series reports (12)(13)(14)(15). Since then, cohort studies (16)(17)(18)(19)(20)(21)(22) have produced sorne evidence of increased cancer risk in systemic lupus erythematosus patients, although the conclusions have not been uniform (23)(24)(25).…”
Section: Il Is Cancer Risk Increased In Systemic Lupus Erythematosus?mentioning
confidence: 99%
See 3 more Smart Citations
“…The earliest clinical evidence of an association of cancer with systemic lupus erythematosus came from case and case series reports (12)(13)(14)(15). Since then, cohort studies (16)(17)(18)(19)(20)(21)(22) have produced sorne evidence of increased cancer risk in systemic lupus erythematosus patients, although the conclusions have not been uniform (23)(24)(25).…”
Section: Il Is Cancer Risk Increased In Systemic Lupus Erythematosus?mentioning
confidence: 99%
“…Attempts to accurately estimate the cancer risk in systemic lupus erythematosus have most often been done with clinical cohorts (18)(19)(20)(21)(22)(23)(24)(25). In a clinical cohort, the subjects have a definite diagnosis of systemic lupus erythematosus, either by American College of Rheumatology criteria (26) or by clinicaljudgment (generaIly, this would mean a patient has definite signs oflupus, such as classic kidney involvement, but doesn't fit exact American College of Rheumatology criteria.…”
Section: Il Is Cancer Risk Increased In Systemic Lupus Erythematosus?mentioning
confidence: 99%
See 2 more Smart Citations
“…SLE patients, by virtue of their disease, have basic defects in immune function that could be increased by the immunosuppressive therapy they receive. Several cohort studies showed an increase of non-Hodgkin's lymphoma (2,3) and of squamous cell skin cancer, especially in patients whose followup was longer than 15 years (4).…”
Section: Introductionmentioning
confidence: 99%